1998
DOI: 10.1007/bf02745680
|View full text |Cite
|
Sign up to set email alerts
|

On the behaviour of organised disturbances in a turbulent boundary-layer

Abstract: This paper is in continuation of our earlier work on the role of hydrodynamic stability theory in understanding wall-bounded turbulent flows. Work in this area was pioneered by Malkus, followed by Reynolds, Tiederman and Hussain. Numerical results showed that the linear instability modes are damped, a result also confirmed by our earlier work for the boundary layer flow case. This led to waning of interest in this approach. In the present work the problem is reformulated using an improved nonisotropic model fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 19 publications
1
22
0
Order By: Relevance
“…A brief outline of the theory will be presented here (details may be seen in Sen & Veeravalli 1998, 2000 In the discussion to follow, the instantaneous velocity vector u i and pressure p obey the incompressible Navier-Stokes and continuity equations. The velocity and pressure fields are usually decomposed in turbulent flows by the well-known Reynolds decomposition; however, here we prefer a triple decomposition as follows:…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…A brief outline of the theory will be presented here (details may be seen in Sen & Veeravalli 1998, 2000 In the discussion to follow, the instantaneous velocity vector u i and pressure p obey the incompressible Navier-Stokes and continuity equations. The velocity and pressure fields are usually decomposed in turbulent flows by the well-known Reynolds decomposition; however, here we prefer a triple decomposition as follows:…”
Section: Theorymentioning
confidence: 99%
“…However, they did not find any region of instability in their theoretical work and this was confirmed by their experiments . Sen & Veeravalli (1998, 2000a) (hereinafter referred to as SV1 and SV2 respectively) considered the problem afresh and concluded that the main reason that the previous investigators failed to find any unstable modes was that they used an isotropic eddy viscosity model, which is really not justified close to the wall. They then derived an extended Orr-Sommerfeld equation based on an anisotropic eddy viscosity model (the eddy viscosity model is similar to the one outlined in Pope 1975).…”
Section: Introductionmentioning
confidence: 98%
“…Their experiments (Hussain & Reynolds,[5]) and theoretical results indicated that hydrodynamic stability theory may not be relevant to wallturbulence. Sen & Veeravalli [6][7] considered the problem afresh and concluded that the inability of previous researchers to find any unstable modes was because of the selection of an isotropic eddy viscosity model, which is really not justified near the wall. Sen & Veeravalli [6][7] used a more realistic anisotropic eddy viscosity model (based on Pope, [8]) and found wall-mode instabilities.…”
Section: Introductionmentioning
confidence: 98%
“…Sen & Veeravalli [6][7] considered the problem afresh and concluded that the inability of previous researchers to find any unstable modes was because of the selection of an isotropic eddy viscosity model, which is really not justified near the wall. Sen & Veeravalli [6][7] used a more realistic anisotropic eddy viscosity model (based on Pope, [8]) and found wall-mode instabilities. The solutions found by Sen & Veeravalli [6][7] mimicked some features of wall bounded turbulent flows like location of the production peak.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation